Supporting and influencing data privacy practice: The free access International Privacy Law Library - Greenleaf, Graham; Chung, Philip; Mowbray, Andrew (Computer law & security review, 2015)
How can legal information institutes (LIIs) providing free online access to legal information, best use their shared resources to assist organisations and individuals involved in data privacy research, complaint resolution and policy development? The International Privacy Law Library (IPLL), located on the World Legal Information Institute (WorldLII) is a resource which attempts to bridge the gap between these two types of organisations. This article explores issues in the development of IPLL, and progress to date in resolving them. We then consider (Part 2) the key problem and our proposed solution to the more general question ‘How can LIIs create and maintain subject-oriented resources economically?’ WorldLII provides free access, via cooperation between seventeen LIIs, to a considerable amount of the information needed, often buried in very large generic databases of case law, legislation or scholarship. The challenge in building IPLL is to pre-select material potentially relevant to privacy issues to create a high value searchable global collection, but to do so on a low and sustainable budget. The resulting International Privacy Law Library (Part 3) is a combination of two main elements: (i) pre-selected databases, some maintained by active provision of data by DPAs, and some built editorially by the LIIs; and (ii) a set of ‘virtual’ databases (one each for case law, legislation, scholarship etc) drawn from all other content found on the LIIs. Once these virtual databases are built, they are self-maintaining (updated daily) and expand as relevant new content is added to any collaborating LII. We conclude (Part 4) with an assessment of future development needs and issues, particularly in relation to multi-lingual materials.